Peg Biology: Deciphering the Molecular Regulations Involved During Peanut Peg Development - Kumar, Rakesh; Pandey, Manish K.; Roychoudhry, Suruchi; Nayyar, Harsh; Kepinski, Stefan; Varshney, Rajeev K. (Frontiers in Plant Science, 2019)
Peanut or groundnut is one of the most important legume crops with high protein and oil content. The high nutritional qualities of peanut and its multiple usage have made it an indispensable component of our daily life, in both confectionary and therapeutic food industries. Given the socio-economic significance of peanut, understanding its developmental biology is important in providing a molecular framework to support breeding activities. In peanut, the formation and directional growth of a specialized reproductive organ called a peg, or gynophore, is especially relevant in genetic improvement. Several studies have indicated that peanut yield can be improved by improving reproductive traits including peg development. Therefore, we aim to identify unifying principles for the genetic control, underpinning molecular and physiological basis of peg development for devising appropriate strategy for peg improvement. This review discusses the current understanding of the molecular aspects of peanut peg development citing several studies explaining the key mechanisms. Deciphering and integrating recent transcriptomic, proteomic, and miRNA-regulomic studies provide a new perspective for understanding the regulatory events of peg development that participate in pod formation and thus control yield.